Attenuation of Multilocal Resonant Coupled Cylindrical-shaped Sonic Crystal with Various Slit Position and Axis Orientation Angle. (2017) - Kristiani, Restu; Yahya, Iwan; Harjana,; Suparmi,; Fitriani, Mustika Cahya
Abstract: Attenuation and frequency response of coupled tubular-shaped sonic crystal with various slit position and axis orientation angle has been analyzed through an experimental approach. The test specimens model is constructed by two cylindrical-shaped resonators with different diameter d 1 and d 2 . Both resonators coupled in a certain configuration with inter-axis distance ( d 1 < a < d 2 ) to form multi-local resonant sonic crystal element. The results show that the attenuation and transmission properties are can be tuned by varying the opening angle of the front resonator and the exit slit of the rear resonator. The tunable narrow band is found occurred at a tiny frequency band between 195 Hz and 256 Hz.